Reuse of decolourised wastewater of azo dyes containing dichlorotriazinyl reactive groups using an advanced oxidation method - (:unkn) unknown (SOC DYERS COLOURISTS, 2001)
The possibility of reusing textile wastewater in dyeing processes is investigated in this study. Wastewater was first decolourised by an advanced oxidation method and was then reused in the dyeing of cotton fabric. It was found that decomposition products of the azo dyes used in this study released hydrogen peroxide and sodium sulphate, which were found to be present in the initial wastewater following decolourisation. Removal of this hydrogen peroxide from the wastewater prior to subsequent dyeings produced a dyeing colour strength of 98.4% as compared to that of the standard dyeing. A second reuse of this wastewater resulted in a slightly lower colour strength of 94.4% as compared to standard dyeing.
Keywords: DECOLORISATION TREATMENTS; WATERS